KAJIAN ISLAM PROGRESIF DAN IJTIHAD PROGRESIF: MEMBACA GAGASAN ABDULLAH SAEED - Yurna Bachtiar; Sihabudin; Siti Sarifah; Jenal Nurhakim; Aang Purnawirawan; Ikbal Fatardo (STKIP Subang, 2026)
This study examines the concept of Progressive Islam and Progressive Ijtihad through an analysis of Abdullah Saeed’s thought as a contemporary Muslim scholar. The main problem addressed in this research is how Islamic teachings can be interpreted contextually to respond to modern challenges while remaining faithful to the core values of the Qur’an. The purpose of this study is to explore Saeed’s framework of progressive ijtihad and its relevance for developing a dynamic and contextual understanding of Islam. This research employs a qualitative library research method, using primary sources from Abdullah Saeed’s works and secondary sources from relevant scholarly literature. The findings indicate that Abdullah Saeed proposes a contextualist approach to Islamic interpretation that emphasizes ethical values, human rights, and social justice, while considering historical context and contemporary realities. Progressive ijtihad, as conceptualized by Saeed, offers an alternative paradigm for Islamic thought that bridges traditional Islamic scholarship and modern societal needs. This approach contributes significantly to the development of Islamic studies by promoting flexibility, inclusivity, and relevance in interpreting Islamic teachings in the modern era.